A Geographical Analysis of the Concentrations of Air Tiny Pollutants PM2.5-PM10 on Walking Paths in the City of Buraidah and Their Relationship to Road Quality - Alkhushiban, Haifa Ali (Journal of natural sciences, life and applied sciences, 2024)
Walking tracks represent one of the most important projects to which the government of the Kingdom of Saudi Arabia has given great attention. To improve the quality of healthy life within cities, this study aims to reveal the temporal and spatial variation of PM10 and PM2.5 concentrations in the paths designated for walking around parks, and compare them with global indicators issued by the US Environmental Protection Agency, and their relationship to the quality of the roads surrounding them, relying on the descriptive approach and the analysis approach and using the statistical program SPSS, where it was done. Identifying six parks within the city of Buraidah, in Al-Qassim region, which meet the conditions for establishing tracks.Accordingly, the results showed that the average concentrations of PM10 and PM2.5 fall within the good and moderate health levels, according to global indicators. The results also showed that there is an effect of the track’s location near highways, as there is an increase in their levels at Al-Uqailat Manakh Park track, which is located on the main road. ; King Fahd Road, Al-Adl Road, and Al-Montazah Park Track, located on King Abdulaziz Road, as for the time level; The results found that there are no statistically significant differences between holiday days, work days, and time period, between the concentrations of tiny particles, except for PM10 levels, if it was found that there was a slight increase during the early morning hours, compared to the evening hours, as the analytical results showed. The density of traffic on the roads surrounding the walking paths; Resulting in an increase in tiny particle rates. Accordingly, the study recommended the necessity of taking into account traffic safety requirements, and environmental and health standards, when determining the locations of walking paths within cities.
Keywords: PM10; PM2.5; Buraidah; walking tracks; traffic roads